Hypnotherapy Intervention Can Reducing Anxiety and Cortisol in Pregnancy - Finta Isti Kundarti; I Nengah Tanu Komalyna (Poltekkes Kemenkes Palu, 2023)
Pregnant women can experience anxiety during pregnancy. To enhance mental health during pregnancy, interventions related to the relation of the mental body are important. The goal of this research was to determine the effect of hypnotherapy on anxiety and cortisol. The present sample consists of 60 primiparous women with single and regular pregnancies, 18-28 weeks gestation, and a randomized control trial. The group consists of the monitoring group (n = 30) and the hypnotherapy group (n = 30). Intervention with hypnotherapy was performed twice for 7 weeks. Assessment of anxiety at baseline and after 7 weeks of intervention by PASS and blood cortisol. Hypnotherapy intervention and quality treatment obtained by the hypnotherapy community; standard care received by the control group. The result show that The hypnosis in pregnancy intervention could significantly decrease anxiety at the lower level than control group (m=21.07 ± SD=11.98 vs m=34.00 ± SD=17.35),. The hypnotherapy in pregnancy intervention could significantly decrease cortisol lower than control groups (m=14.64, ± SD=5.53 vs m=21.51, ± SD=8,83). The conclusion is intervention with hypnotherapy may enhance pregnant women's mental health, as shown by reducing anxiety and cortisol. Hypnotherapy is an intervention that needs to be provided during pregnancy in midwifery programs to improve the health of mothers and babies.